Relationship of PD-1 (PDCD1) and PD-L1 (CD274) Single Nucleotide Polymorphisms with Polycystic Ovary Syndrome. (4th January 2021) - Han, Rui; Gong, Xiaoyun; Zhu, Yuejie; Liu, Xiaoran; Xia, Yan; Huang, Yuhong; Zhang, Meng; Zhang, Yunian; La, Xiaolin; Ding, Jianbing
Abstract : This study is to investigate the relationship of programmed cell death 1 (PD-1; also known as PDCD1) and programmed death-1-ligand 1 (PD-L1; also known as CD274) single nucleotide polymorphisms (SNPs) with polycystic ovary syndrome (PCOS). This study enrolled 330 PCOS patients and 350 matched controls. ELISA was used to detect the PD-1 and PD-L1 levels in serum. SnaPshot genotyping was performed to analyze the PD-1 and PD-L1 genotyping. Linkage disequilibrium and haplotype of TagSNP loci of PD-1 and PD-L1 genes were also detected. The relationship of genotypes and alleles with PCOS was analyzed. The levels of PD-1 and PD-L1 in the serum of PCOS patients were significantly lower than those in the control group (P < 0.01 ). The haplotype TT of PD-1 gene at rs10204525 and rs7421861 loci was significantly lower in the PCOS group than in the control group (P < 0.001, OR = 0.67, and 95 % CI = 0.54 ‐ 0.84 ). PD-L1 gene SNP loci rs2282055, rs2890658, rs10125854, and rs702275 had linkage disequilibrium. The haplotypes TAAA, GAAC, GAGC, GCAA, and TCGA of PD-L1 gene SNP loci were significantly higher in PCOS patients than in the control group, whereas haplotypes GAAA, TAAC, TCAA, GCGA, GCAC, and TCGC of PD-L1 gene SNP loci were significantly lower in PCOS patients than in the control group. PD-1 and PD-L1 SNPs may be related to the pathogenesis of PCOS. PD-1 gene SNP loci rs10204525 and rs7421861 and PD-L1 gene SNP loci rs2282055, rs2890658, rs10125854, and rs702275 may be new candidate polymorphic loci for PCOS.